Application of The Lesson Study-Based Problem Learning Model To Improve Communication Skills And Teamwork Skills Of Biological Education Students - Miftahussaadiah Miftahussaadiah (IJER (Indonesian Journal of Educational Research), 2021)
This study aims to determine the application of the Problem Based Learning (PBL) learning model to improve communication skills and teamwork skills for Biology Education Students. The subjects of this study were students who offered C PPG in 2016 odd semester of the 2018/2019 academic year S1 Biology Education, State University of Malang. Data on communication skills in the form of scores obtained from the rubric of writing communication skills based on observations. Teamwork Skills consist of observation sheets filled out by observers and questionnaires filled out by students at each meeting. The results showed that: (1) LKM students' communication skills in each meeting increased, namely in cycle one 1 in the content aspect from 72.41% to 95.15%; organizational aspects from 80.17% to 91.34%; syntax aspect 71.55% to 72.11%; views and information 55% to 75%. (2) Student Teamwork Skills have increased, namely aspects of focus on goals from 83.07 to 83.84%, Leadership and ownership (75.38 to 81.35 %), Delegation of tasks (71.53 to 74.23) %, and time management (79.23 to 54.61) %. The conclusions of this study are: learning using a problem based learning (PBL) model based on lesson study can improve students' communication skills, especially writing and student Teamwork Skills.